Sensitization and desensitization of burn patients as potential candidates for vascularized composite allotransplantation. Issue 2 (March 2016) - Klein, H.J.; Schanz, U.; Hivelin, M.; Waldner, M.; Koljonen, V.; Guggenheim, M.; Giovanoli, P.; Gorantla, V.S.; Fehr, T.; Plock, J.A.
Highlights: Blood transfusions and cadaveric skin coverage can lead to sensitization. Thorough administration of blood transfusions or cadaveric skin is needed. VCA performed as primary reconstruction could obviate the issues of sensitization. Abstract: Sensitization describes the acquired ability of the immune system to react to foreign human leukocyte antigens (HLA) by producing antibodies and developing memory cells. In the field of transplantation, recipient preformed HLA antibodies due to previous sensitization have been identified – beneath ABO incompatibility – as a major factor for acute graft rejection. Several reasons for sensitization have largely been studied, such as previous blood transfusions, pregnancies or former transplants. Recent studies indicate that the use of assist devices (e.g. ECMO) or cadaveric skin allotransplantation providing temporary coverage in burn patients may lead to additional sensitization. As vascularized composite allotransplantation (VCA) has become a rapidly advancing therapeutic option for reconstruction of complex tissue defects in burns, it seems even more important to become familiar with immunological principles and to be cautiously aware of both sources of sensitization and therapeutic concepts in burns avoiding sensitization. This may also include emergency VCAs in burn patients as potential strategy for early definitive reconstruction avoiding procedures triggering HLA antibody formation. We hereby provide an overview on current evidence in the field of pre- and peritransplant sensitization, followed by posttransplant strategies of desensitization and their potential impact on future treatments of burn patients.